PARTISIPASI MASYARAKAT PADA PENGAWASAN PEMBANGUNAN DI DESA TARIPA KECAMATAN PAMONA TIMUR KABUPATEN POSO - TOBADE, ALFRIYANTO; TAMPI, GUSTAAF BUDDY; RURU, JOORIE MARHAEN (Sam Ratulangi University, 2019)
Community participation in supervision of development in Taripa Village, the low levelof community participation is due to several factors, for example during meetings or Village meetings,representatives who attend are very minimal, the cause of community absence is the activities of thecommunity who have to work, there is also a factor in low community participation on the supervisionof development is the minimal mindset of the people who consider development to be the responsibilityof the government. The purpose of the study was to determine community participation in monitoringdevelopment in Taripa Sub-District, East Pamona Sub-District, Poso Regency. The research methodused in this research is descriptive qualitative research method. Data collection techniques used areobservation, interviews and data collection with documents. Based on the results of the research anddiscussion, the authors draw conclusions about Community Participation in the DevelopmentSupervision of Taripa Village, East Pamona Sub-District, Poso Regency: Community participation insupervision of development can be said to run well even though there are still people who do not takepart in planning and supervising existing development. The supervision carried out by the communitytowards development in the village of Taripa has experienced an increase where most of the developmentcarried out goes well according to what was previously planned. Suggestions that can be given includethe need for coordination between the village government and the community in implementingdevelopment. The community is expected to participate in development planning and supervision. Theneed for the village government to provide clear information to the community regarding thedevelopment that will be carried out.Keywords: Community Participation, Civil Service, development